Philosophy of management and sustainability : rethinking business ethics and social responsibility in sustainable development - Rendtorff, Jacob Dahl (Emerald Publishing Limited, 2019)
Using an interdisciplinary focus, this book combines the research disciplines of philosophy, business management and sustainability to aid and advance both scholarly and practitioner understanding of sustainability management and the United Nations' Sustainable Development Goals (SDGs). As businesses and society continue to transition towards further sustainable development and corporate social responsibility, the key challenge faced is in rethinking the philosophy of management and business ethics to achieve this change in deep and lasting ways. Jacob Dahl Rendtorff explores the philosophical foundations of business ethics, economics and sustainability through four key themes: From CSR and business ethics to sustainable development goals (SDGs) Philosophy of management and ethical economy of sustainability Foundations of philosophy of management, ethics and sustainability Responsible management of sustainability. In reflecting on the works of philosophers and scholars such as Hannah Arendt, Paul Ricœur, Thomas Piketty and Peter Koslowski within the context of sustainability, globalization, anthropocene ethics and corporate social responsibility, the book presents a key understanding of the vital philosophical foundations for creating progressive business models in a more sustainable society.- Resumé vydavatel
Includes index.
Keywords: manažerská etika; udržitelný rozvoj; management; filozofie; business ethics; sustainable development; philosophy; elektronické knihy; monografie; electronic books; monographs